Clinical application of plasma exchange combined with early continuous renal replacement therapy in patients with multiple injuries and high myoglobinemia - REN Hongbing; ZHANG Yuansong; ZHU Haoran (陆军军医大学学报)
Objective‍　‍To explore the clinical safety of plasma exchange (PE) combined with early continuous renal replacement therapy (CRRT) and its effects on coagulation and immune functions in patients with polytrauma and hypermyoglobinemia. Methods‍　‍A non-randomized controlled study was conducted on 60 patients with severe polytrauma and myoglobinemia hospitalized in our department from January 2021 to December 2024. Based on different blood purification, the patients were divided a control group (CRRT) combined with conventional basic treatment, n=30) and an observation group (PE+CRRT and conventional basic treatment, n=30). Biochemical indicators (myoglobin, Mb), inflammation-related indicators, peripheral blood lymphocyte subsets, coagulation indicators, clinical-related indicators, and scores were observed and compared between the 2 groups before and after treatment. Results‍　‍After 1, 2 and 3 d of treatment, the levels of Mb, creatine kinase (CK), creatine kinase-MB isoenzyme (CK-MB), lactate dehydrogenase (LDH), serum creatinine (SCr), blood urea nitrogen (BUN), K+, C-reactive protein (CRP), procalcitonin (PCT), IL-6 and D-dimer (D-D), and white blood cell (WBC) count were significantly decreased in both groups (P<0.05). Among them, the observation group obtained obviously lower levels of all above indicators than the control group at the 3 time points (P<0.05). Additionally, notably shorter average length of total hospital stay, shorter average length of trauma intensive care unit stay, and lower score of acute physiology and chronic health evaluation Ⅱ (APACHEⅡ) was observed in the observation group than the control group (P<0.05). There were no statistical differences in coagulation function indicators or T lymphocyte subsets between the 2 groups. No complications occurred. Conclusion‍　‍For patients with polytrauma and hypermyoglobinemia, early application of PE+CRRT can effectively reduce serum myoglobin level, improve serum biochemical inicators, renal function and inflammatory status, and maintain homeostasis, but shows no effect on immune or coagulation functions. This approach is worthy of promoting in clinical practice.